Analisis Laporan Keuangan Yayasan Islam Hasan Kafrawi - Ana Ivatul Khoni’ah; Aida Nahar (Jurnal Rekognisi Akuntansi, 2021)
This study aims are to determine the use of SI Apik system in compiling financial reports at the Hasan Kafrawi Islamic Foundation and to determine the suitability of the Si Apik application financial reports with PSAK No. 45. The object in this study is the Hasan Kafrawi Pancur Mayong Islamic Foundation, Jepara. The method of this research is research and development. Researchers used a qualitative approach with descriptive analysis technique methods. Data collections in this research are observation, interviews and documentation. Based on the results of the researcher's analysis, it can be seen that the Si Apik application can fulfill what the company needs in the company's operational activities in the revenue cycle and the expenditure cycle easily, practically and efficiently. Reporting using the Si Apik application is not in accordance with PSAK No. standard aspects of PSAK No. 45